Matrix-tilted Archimedean copulas - Marius Hofert; Johanna F. Ziegel (Risks, 2021)
The new class of matrix-tilted Archimedean copulas is introduced. It combines properties of Archimedean and elliptical copulas by introducing a tilting matrix in the stochastic representation of Archimedean copulas, similar to the Cholesky factor for elliptical copulas. Basic properties of this copula construction are discussed and a further extension outlined.
Keywords: 330; Archimedean copulas; elliptical copulas; generalization; stochastic representation; tilting